Learning to use electronic health records: can we stay patient-centered? A pre-post intervention study with family medicine residents - Cédric Lanier; Melissa Dominicé Dao; Patricia Hudelson; Bernard Cerutti; Noëlle Junod Perron (BMC Family Practice, 2017)
Abstract Background The Electronic Health Record (EHR) is now widely used in clinical encounters. Because its use can negatively impact the physician-patient relationship, several recommendations on the “patient-centered” use of the EHR have been published. However, the impact of training to improve EHR use during clinical encounters is not well known. The aim of this study was to assess the impact of training on residents’ EHR-related communication skills and explore whether they varied according to the content of the consultation. Methods We conducted a pre-post intervention study at the Primary Care Division of the Geneva University Hospitals, Switzerland. Residents were invited to attend a 3-month training course that included 2 large group sessions and 2–4 individualized coaching sessions based on videotaped encounters. Outcomes were: 1) residents’ perceptions regarding the use of EHR, measured through a self-administered questionnaire and 2) objective use of the EHR during the first 10 min of patient encounters. Changes in practice were measured pre and post intervention using the Roter interaction analysis system (RIAS) and EHR specific items. Results Seventeen out of 27 residents took part in the study. Participants used EHR in about 30% of consultations. After training, they were less likely to consider EHR to be a barrier to the physician-patient relationship, and felt more comfortable using the EHR. After training, participants increased the use of signposting when using the EHR (pre: 0.77, SD 1.69; post: 1.80, SD3.35; p 0.035) and decreased EHR use when psychosocial issues appeared (pre: 24.5% and post: 9.76%, p < 0.001). Conclusions This study suggests that training can improve residents’ EHR-related communication skills, especially in situations where patients bring up sensitive psychosocial issues. Future research should focus on patients’ perceptions of the relevance and usefulness of such skills.